Global Mixed Race - King-O'Riain, Rebecca C. (King-O'Riain, Rebecca Chiyoko) (Book collections on Project MUSE., 2014)
Examines the contemporary experiences of people of mixed descent in nations around the world, moving beyond US borders to explore the dynamics of racial mixing and multiple descent in Zambia, Trinidad and Tobago, Mexico, Brazil, Kazakhstan, Germany, the United Kingdom, Canada, Okinawa, Australia, and New Zealand